Interglacial diversity - Tzedakis, PC; Raynaud, D; McManus, JF; Berger, A; Brovkin, V; Kiefer, T (NATURE PUBLISHING GROUP, 2009)
Earth's climate has progressively cooled over the past 3 million years with a concomitant expansion of continental ice volume. This global trend towards increasingly severe and extended ice ages has nevertheless been repeatedly interrupted by relatively mild/warm interglacial intervals such as the one that has characterized the past 11,000 years. Past interglacials can be thought of as a series of natural experiments in which climate boundary conditions varied considerably, with consequent effects on the character of climate change. As such they can provide a more complete view of the range and underlying physics of natural climate variability. Examination of the palaeoclimate record of the past 800,000 years reveals a large diversity among interglacials in terms of their intensity, duration and internal variability, but a general theory accounting for this diversity remains elusive. Future work should focus on generating new palaeodata and modelling interglacial diversity, and using this information to inform projections on the future evolution of the current interglacial.